Kinetic Analysis of Neurotrophin-3–Mediated Differentiation of Embryonic Stem Cells into Neurons - Willerth, Stephanie M. (Mary Ann Liebert, Inc., 2009)
The goal of this study was to develop a kinetic analysis that could predict the behavior of embryonic stem cell-derived neural progenitor cells (ESNPCs) in response to treatment with neurotrophin-3 (NT-3). Previous studies have shown that NT-3 activates the mitogen-activated protein (MAP) kinase cascade in embryonic stem cells and promotes differentiation of ESNPCs into neurons. MAP kinase activation after NT-3 stimulation was confirmed experimentally, and a kinetic analysis was developed using rate constants obtained from the literature. Concentrations of select signaling components were estimated for ESNPCs using real-time reverse transcription polymerase chain reaction by comparing mRNA levels to those of cell types with known protein concentrations. This assumption was validated using Western blots, and incorporated into the analysis. This analysis was used to predict the minimum NT-3 concentration necessary to promote neuronal differentiation of ESNPCs based on the activation of MAP kinase. These predictions were then tested experimentally to confirm the validity of the analysis. Finally, expression of the transcription factor mammalian achate schute homolog 1 and β-tubulin III (an early neuronal marker) was examined in response to the different NT-3 doses to confirm the link between MAP kinase activation and neuronal differentiation. Overall, this study provides insight into the kinetics of the intracellular processes that promote ESNPC differentiation to neurons.